"Beauty cajoles": Friedrich Schiller and the Aesthetic Education of Rhetoric. Issue 2 (15th March 2017) - Stoneman, Ethan
Abstract : Friedrich Schiller may not be a household name among contemporary rhetoricians, yet since the 1960s Schiller's critics have begun to take an interest in the rhetorical dimension of his aesthetic writings, particularly with respect to his Aesthetic Letters . These efforts, however, tend to focus on Schiller's method of presentation rather than the possible rhetorical implications of the Letters ' key ideas and concepts. This essay proposes treating the Letters as an instance of implicit rhetorical theory, one that suggests an innovative model of rhetorical effectivity, according to which rhetoric enables people to experience the normative ideal of beauty as freedom.